Bank lending and monetary transmission in the euro area - Roberto A. De Santis; Paolo Surico (European Central Bank (ECB), 2013)
To what extent does the availability of credit depend on monetary policy? And, does this relationship vary with bank characteristics? Based on a common source of balance sheet data for the four largest economies of the euro area over the period 1999-2011, we uncover three main regularities. First, the effect of monetary policy on bank lending is significant and heterogeneous in Germany and Italy, which are characterised by a large number of banks; but it is very weak in Spain and more homogeneous in France, where the banking industry has a higher degree of market concentration. Second, there is some evidence that monetary policy exerts larger effects on cooperative and savings banks with lower liquidity and less capital in Germany and savings banks with smaller size in Italy. Third, heterogeneity across groups of banks belonging to the same category in any particular country is found to be less pronounced.
Keywords: C33; E44; E52; G21; 330; commercial; cooperative; credit availability; heterogeneous effects; monetary policy; savings banks